(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
On Dec. 1, 2019, the initial COVID-19 cases were documented, with the cause being a then-new coronavirus called as severe acute respiratory illness coronavirus 2. (SARS-CoV-2). SARS CoV-2 may have begun in animals and advanced into a human infectious illness. Virus that evolved in eagles, pigs, dogs, and various Animals have developed in the previous to be deadly to people, resulting in several outbreaks of infectious illness. The novel coronavirus 2019 (COVID-19) has been recognized the World Health Organization has confirmed it a universal community fitness emergency. Since, the epidemic has dominated the front pages of major worldwide news outlets that convey information to the world’s inhabitants. However, owing to the epidemic being dubbed "Chinese viral pandemonium," some media reporting of COVID-19 has had a severe impact on Chinese travelers’ mental health. President Donald Trump, for example, referred to COVID-19 as the "Chinese virus" in a tweet. Violent assaults against Chinese overseas travelers and students have occurred from this discriminatory labeling. During the worldwide COVID-19 outbreak, this viewpoint piece examines how false and discriminating media stories may impair the mental health of ethnically Chinese travelers. The future scope of this study is that media is the cheapest and fast way of spreading information.